Identificação das variáveis que ocasionam a variação de tonalidade utilizando a técnica de decoração por cilindros de silicone gravados a laser - Ferraço, Fabio (2015)
A major problem in the production of ceramic tiles for coating is the variation of tonality. The determination of their origin within the entire production process and to minimize its occurrence by the manufacturer is essential. In 2014 the production was 903.3 million square meters, with an estimate production for 2015 of 969.3 million square meters, which justifies studies of varying shades in production lines ceramic tiles. For the execution of this work, some variables will be fixed without any loss in accuracy of the results to be obtained, if only because some of them are already inherent in the product development flow: ink (formulation); type of glaze and engobe, decorating cylinder characteristics (type of silicone, incisions, cylinder size), basic design, set-up decoration equipment and operating condition. The variables studied were: Density and viscosity of silkscreen ink; Temperature of the ceramic carrier; Production speed; Cylinder pressure on the tile; Blade Pressure on the cylinder; Blade angle of attack and support surface humidity. It was observed that the variables density and viscosity; Decorating speed and variation of blade height on the cylinder are the variables that most affect the tone variation factor within a production. For the three cases studied, none of the incisions resulted in filling and form an ideal decorated dot regarding to the expected geometry and desired for an ideal decoration (spherical points or ellipse) in any of the tested variables. In all cases there is a maximum point reached by the variables studied, which gave a better discharge and consequently a better decoration. In each tone range studied there is a combination of variables which best accomplishes the deposition points on the enamel.